Group Polarization in Board Decisions About CEO Compensation - Zhu, David H. (Organization Science, 2014)
This study examines how chief executive officer (CEO) compensation decisions may be influenced by a major group decision-making tendency referred to as group polarization among outside directors. I start by explaining why outside directors on average tend to support relatively high (low) CEO compensation when they previously witnessed relatively high (low) CEO compensation across different boards. Group polarization theory then suggests that when outside directors on average tend to support relatively high (low) CEO compensation prior to board discussions, they will support even higher (lower) focal CEO compensation after the discussions. In addition, this study proposes three important moderators of the group polarization effect. Specifically, (1) demographic homogeneity among outside directors and (2) the similarity of the minority’s prior decision context are proposed to weaken the group polarization effect, whereas (3) outside directors’ power relative to inside directors is predicted to strengthen it. Longitudinal analyses (1995–2006) of Fortune 500 CEOs’ compensation provide support for these theoretical predictions. This study contributes to corporate governance research on CEO compensation by advancing a novel group decision-making approach to examining this important decision.